Analysis of Quality Management in Improving Competitiveness in Sustainable Pottery Businesses - Aslami, Nuri; Ikhwan, Ali; Apriani, Ari (International Conference on Sciences Development and Technology, 2023)
This study aims to analyze the implementation of quality management in improving competitiveness at Tembikar Lestari. Using descriptive qualitative methods, this research explores how the management of raw materials, production techniques, and marketing strategies impact the competitiveness of pottery products. The results show that the use of local quality raw materials, the application of rotary production techniques, and the adaptation of modern and traditional technologies in the firing process synergistically improve product quality. Marketing strategies through MSME bazaar participation and socialmedia promotion proved effective in expanding the market to various regions in North Sumatra, Aceh and Riau. Word-of-mouth and social media effects also play an important role in increasing consumer buying interest. The main obstacle faced is the limited delivery system, which restricts wider market access. The findings confirm that quality management integrated with marketing strategy is key to building the competitiveness of small and medium-sized enterprises, especially in the creative industry sector.